2019
DOI: 10.17269/s41997-019-00212-5
|View full text |Cite
|
Sign up to set email alerts
|

Drinking motives supporting binge drinking of Inuit adolescents

Abstract: Objectives Binge drinking has been identified as a public health concern among several Indigenous communities in Canada. Drinking motives have been shown to significantly influence drinking patterns among youth, but no research has been conducted among Inuit populations. This article assesses whether specific drinking motives are related to the number of binge drinking episodes among Inuit adolescents from Nunavik. Methods The data are drawn from the Nunavik Child Development Study, a longitudinal study conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…In particular, the enhancement motive of the five motives significantly predicted both binge and high-risk drinking. These findings are consistent with research reporting that enhancement motives are the frequent drinking motivation reported among adolescents [ 13 ], with young adults [ 15 , 26 ] engaging in binge drinking. The social and conformity motives predicted only binge drinking and not high-risk drinking.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In particular, the enhancement motive of the five motives significantly predicted both binge and high-risk drinking. These findings are consistent with research reporting that enhancement motives are the frequent drinking motivation reported among adolescents [ 13 ], with young adults [ 15 , 26 ] engaging in binge drinking. The social and conformity motives predicted only binge drinking and not high-risk drinking.…”
Section: Discussionsupporting
confidence: 92%
“…They also drank more and were significantly more likely to be binge drinkers or high-risk drinkers. Among the respondents, norms served as a standard for judging the appropriateness of their actions by observing others’ drinking behavior [ 5 , 8 , 13 ]. Consistent with prior research, the individuals in our study who overestimated the frequency and quantity of alcohol use by others were the heaviest drinkers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations